Modelling tourism demand: an augmented gravity model - Jong, Meng-Chang; Puah, Chin-Hong; Mohammad Affendy Arip (Penerbit Universiti Kebangsaan Malaysia, 2020)
This paper aims to investigate the factors affecting tourism demand in Sabah using an augmented gravity model. In modelling tourism demand, a balanced panel data set of ten countries over 2010-2016 is analyzed using the static panel data approach. The income levels in tourist origin countries and the income level in Sabah are positively affecting Sabah tourism demand. Meanwhile, transportation costs and tourism prices adversely influence tourism demand in Sabah.